A pictural guide to postmortem examination of elephants - Almuth Falkenau; Ninja Kolb; Alexandra Rieger; Isabelle Lutzmann; Katharina Erber; Clara Kaufhold; Lina Eddicks; Marco Rosati; Sonja Fiedler; Anna Gager; Effrosyni Michelakaki; Elena Dell’Era; et al. (PLoS ONE, 2026)
The necropsy of an elephant represents a rare event for most veterinary pathology facilities outside of Africa and Asia. Here, we report a comprehensible, abundantly illustrated, step-by-step protocol adapted to the special technical and anatomical peculiarities of elephant necropsies with regard to the needed equipment, aspects of transmissible disease prevention and workplace safety, personnel, time efforts, as well as important elephant diseases and their zoonotic potential. Detailed instructions for dissection, macroscopic examination and sampling of all relevant organs and tissues are provided, along with checklists for preparation and smooth execution of elephant necropsies. Using the featured protocols, a complete elephant necropsy with generation of extensive samples for histological, microbiological, and molecular analyses can be performed by 10–12 persons (5–6 pathologists and 5–6 assistants) within 4–6 hours in case of an adult animal.